INFLUENCE OF A LOW-MOLECULAR FRACTION (below 5 kDa) FROM CORD BLOOD AS AN EYE GEL COMPONENT ON CORNEA REGENERATION AFTER MECHANICAL DAMAGE - Dyomin, Yu.A.; Gulevsky, A.K.; Seydaliyeva, Z.A.; Volina, V.V.; Moiseyeva, N.N. (World of Medicine and Biology, 2013)
The influence of a low-molecular fraction (below 5 kDa) from human cord blood (HCBF) as an eye gel component on cornea regeneration was studied in an experimental model of mechanical damage. Histomorphological analysis showed that the application of the HCBF-containing gel accelerated differentiation of frontal epithelium in the area of cornea lesion, normalization of stroma structure and restoration of its transparency in shorter terms than the reference drug Actovegin® did after mechanical damage. The data obtained require further investigations of mechanisms of action of HCBF as an eye gel component on reparative processes in damaged cornea aimed at developing new ophthalmologic methods and approaches for cornea defect treatment, which could prevent development of inflammatory complications and blindness.
Keywords: cornea regeneration; low-molecular fraction (below 5 kDa) from human cord blood; Actovegin®